THE HUMAN FACTOR CAPABILITIES IN SECURITY OPERATION CENTER (SOC). Issue 1 (3rd July 2022) - Chamkar, Samir Achraf; Maleh, Yassine; Gherabi, Noreddine
Abstract: The human factor is considered the weakest link in cybersecurity and inside the Security Operation Centers (SOC) and it represents the most important component at the same time. Human factor capabilities and challenges attracted the attention of researchers to address how these challenges can be reduced or mitigated. However, these research papers do not consider the complexity, unpredictability, interdependent and evolving nature of the SOC systems. This study aims to explore the human capabilities and weaknesses inside the Security Operation Centre. To this end, we employed survey bases questionaries alongside the daily observation of SOC analysts and interviews with SOC experts. Forty SOC analysts and five experts conducted the survey. The finding of this study will help SOC managers and SOC designers better understand the challenges faced by the SOC analysts and take into account the interdependent and evolving nature of the Security Operation Centers.